Shear Behavior of Reinforced Concrete Beam using Cold-drawn Steel wire Stirrup - Ketiyot, Rattapon; Hansudewechakul, Chetsadaphong; Chaimahawan, Preeda (RMUTL Engineering Journal, 2022)
This paper presents a shear behavior of six reinforced concrete beam having different of transverse reinforcement detailing and material. The test specimens can be divided into two material groups. For the first one, tie stirrup using SR24 grade round bar with 6.0 mm. in diameter was used as transverse reinforcement with spacing distance as 0.125 and 0.375 m. For the other, spring stirrup using 3.3 mm. in diameter cold drawn steel wire according to TIS 747-2531 with spiral spacing as 0.05 0.075 0.125 and 0.20 m. was applied to transverse reinforcement. All test specimens were carefully tested under static loading according to the third-point load testing. The test results showed that shear capacities of the test specimens with tie stirrup, 0.125 m. spacing distance, and spring stirrup, 0.05 and 0.075 m spacing distances were very similar. Furthermore, the failure mode of the specimens was ductile failure.